Ovocidal action of disinfectants against eggs of Passalurus ambiguus - A. Khorolskyi (Ukrainian Journal of Veterinary and Agricultural Sciences, 2022)
Successful elimination of helminthic diseases, as well as their further prevention, is possible only under the condition of carrying out a complex of organizational and economic, veterinary and sanitary, and special anti-parasitic measures, which must necessarily include disinfestation of places where animals are kept, as well as environmental objects. It is necessary to establish the ability of modern chemical agents to harm certain types of parasites. The research aimed to determine the ovocidal efficiency of disinfectants in different concentrations and exposures against Passalurus ambiguus eggs isolated from domestic rabbits. An experimental test was carried out in laboratory conditions on chemical products of domestic production “Virosan”. (AS – alkyldimethylbenzylammonium chloride, glutaraldehyde) and “Hermecid-VS” (AS – didecyldimethylammonium chloride, glutaraldehyde, benzalkonium chloride). The leading indicator of the effect of disinfectants on the eggs of pasaluris was the value of their disinfestation efficiency. The results of the conducted studies established a high level of ovocidal efficiency of “Virosan” (OE – 100 %) against P. ambiguus eggs at 0.25 % concentration for exposures of 30–60 minutes and 0.5 % concentration for exposures of 10–60 minutes. A satisfactory level of the ovocidal efficiency of “Virosan” was established when using the agent in 0.1 % (30–60 min exposure) and 0.25 % (10 min exposure) concentrations, OE ranges from 62.36 to 82.20 %. An unsatisfactory level of the ovocidal efficiency of “Virosan” was established at 0.1 % of the concentration after exposure for 10 minutes (AS – 47.30 %). Disinfectant “Hermecid-VS” showed a high level of ovocidal efficiency concerning the eggs of pasaluris in 0.1 % concentration for 60 min exposure (OE – 91.45 %) and in 0.25–0.5 % concentration for 10–60 min exposure (AS – 100 %). A satisfactory ovocidal efficiency of “Hermecid-VS” was established when using the product at a concentration of 0.1 % (10 and 30-minute exposures), where OE indicators were 76.25 and 81.91 %, respectively. The obtained data make it possible to recommend disinfectants of domestic production “Virosan” and “Hermecid-VS” in specified concentrations and exposures to control and prevent pasalurosis in rabbits in order to effectively carry out the deinvasion of environmental objects and places where animals are kept.